2020
DOI: 10.1142/s0217590820460030
|View full text |Cite
|
Sign up to set email alerts
|

Do Oil Price Fluctuations Affect the Inflation Rate in Indonesia Asymmetrically?

Abstract: Changes in the oil price directly affect production costs, and subsequently, the general price level of products. With Indonesia observing an inflation targeting policy, this study applies the nonlinear autoregressive distributed lag (NARDL) technique to investigate the effect of oil price fluctuations in Indonesia. The relationship is important for the central bank to gauge the effectiveness of the inflation targeting policy in immunizing the country from oil price fluctuations. Our findings have revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Again, we observe that in the very short run inflation impacts negatively on GDP growth. Our results support that of (Goh, 2022;Akinsola and Nicholas, 2020;Mork et al, 1989 andBrinin et al, 2016). Our findings on foreign direct investment show that in the very short run foreign direct investments increases the rate of growth of GDP but do not have any significant effect on GDP growth in the long run.…”
Section: Presentation and Discussion Of Estimated Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Again, we observe that in the very short run inflation impacts negatively on GDP growth. Our results support that of (Goh, 2022;Akinsola and Nicholas, 2020;Mork et al, 1989 andBrinin et al, 2016). Our findings on foreign direct investment show that in the very short run foreign direct investments increases the rate of growth of GDP but do not have any significant effect on GDP growth in the long run.…”
Section: Presentation and Discussion Of Estimated Resultssupporting
confidence: 92%
“…Using GMM model for 113 economies, Khan and Hanif (2020) found that institutional quality affects economic while they found a negative relationship between inflation and economic growth. Goh et al (2022) observed an asymmetric behaviour between inflation and petroleum prices which in turn impacts negatively on economic growth. Similarly, using GMM approach for North African countries to examine the connection between economic growth and institutional quality, Boujelbene (2021) observed a non-linear nexus among the variables while inflation had a negative effect on economic growth.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Gylych et al (2020) found oil prices as a strong determinant factor of exchange rate, cost of borrowing and inflationary tendencies. Again, Goh et al (2022) found an asymmetric behaviour between oil price and inflation rate and that increase in oil prices in the long run increases inflation.…”
Section: Review Of Empirical Studiesmentioning
confidence: 92%
“…Many studies pay attention to the asymmetric impact of oil prices on inflation. Goh et al (2022) indicate that in Indonesia, in the long run, an increase in oil price tends to increase the inflation rate with a larger deviation, and a decrease in oil price tends to reduce the inflation rate with a smaller deviation. On this basis, they conclude that consumers do not benefit from lower oil prices.…”
Section: Literature Reviewmentioning
confidence: 99%